The Impossible is Possible: Hartarto Sastrosoenarto and Industrialization in Indonesia, 1983 â 1993 - Tangkilisan, Yuda B (ASPENSI in Bandung, Indonesia, 2012)
ABSTRACT: Hartarto Sastrosoenarto was an Indonesian statesman that hold some ministerial offices during the New Order and in the beginning of the Reformation era. He has a big concern for the development of industry in Indonesia. This article deals with his thoughts, experiences, achievements, and vision about how to make Indonesia as a world player in the industrial field in the future. âThe impossible is possibleâ is his phrase that shows his optimism. From his life journey, he had a good opportunity to continue his education from ITB (Bandung Institute of Technology) to Australia. After the completion, he joined the Department of Industry. His academic background and experience brought him to run some industrial projects and then becoming the Minister of Industry in 1984. He began with the reorganization and the development of human resources. Besides, he raised such Main Strategic and Supporting Strategic Policies as a guideline to build the industry. He also paid attention to the small scale industry as the national advantage. Finally, he has a wish that Indonesia will be a world player in the international economics in the future.Â Â Â KEY WORDS: Hartarto Sastrosoenarto, the impossible is possible, industrialization, world player, Indonesian nation-state.About the Author: Dr. Yuda B. Tangkilisan is a Lecturer at the Department of History, Faculty of Humanities UI (University of Indonesia), UI Campus, Depok, West Java, Indonesia. He can be reached at: yebete@yahoo.comHow to cite this article? Tangkilisan, Yuda B. (2012). âThe Impossible is Possible: Hartarto Sastrosoenarto and Industrialization in Indonesia, 1983 â 1993â in TAWARIKH: International Journal for Historical Studies, Vol.4(1) October, pp.83-102. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 19, 2012); Revised (September 21, 2012); and Published (October 28, 2012).